Implementation of IOM in Uganda Utilizing the EPIS Framework: Report of a Symbiotic Collaboration. - Montejano, Julio; Nantongo, Betty; Klumpp, Tessa; Djoyumm, Teguo Daniel; Lahiri, Joshua; Watiti, Daniel; Okechi, Humphrey; Wegoye, Emmanuel; Simmons, Colby (Journal of Central Nervous System Disease, 2025)
Objectives: Low- and lower-middle-income countries (LMICs) bear a disproportionately high burden of neurosurgical disease while facing severe shortages of trained neurosurgeons and anesthesiologists. Access to advanced technologies such as intraoperative neuromonitoring (IONM), crucial for complex neurosurgical procedures, is virtually nonexistent due to infrastructural, educational, and financial barriers. This study describes the development and implementation of Uganda's first IONM program at Cure Children's Hospital of Uganda (CCHU), using the well validated Exploration, Preparation, Implementation, and Sustainment (EPIS) framework. Methods: In collaboration with the University of Colorado, a standardized non-traditional training pathway was created, combining remote and in-person instruction in neurophysiology, technical IONM applications, and anesthetic considerations. Over a 3-year period, the program enabled CCHU to safely perform more than 80 complex pediatric neurosurgical cases across 2 years, incorporating modalities such as somatosensory evoked potentials (SSEPs), motor evoked potentials (MEPs), and electromyography (EMG). Surgical and patient outcomes were not tracked for the purposes of this implementation study. Results: Between March 2022 and October 2024, 80 surgeries were performed at CCHU that made use of IONM technologies. The vast majority of the surgeries were intracranial and included one awake tumor resection with direct cortical mapping (DCS). A smaller subsect of patients underwent spine surgery for either tumor removal or correction of spinal cord tethering. Due to the difficulty in patient outreach many patients were lost to follow-up, however, efforts are being made to track patients and examine their clinical outcomes. Conclusion: Despite resource limitations, this initiative demonstrated that IONM can be effectively integrated into LMIC healthcare settings, improving surgical safety and outcomes while contributing to local workforce development. The success of this program underscores the value of international partnerships and implementation science in bridging global neurosurgical disparities and suggests a scalable model for future adoption across similar contexts.